Smart Locker Menggunakan Fingerprint dan Face Recognition sebagai Sistem Keamanan Loker Penyimpanan - Koesmarijanto; Hidayati, Nurul; Dista Dwi Cahyani; Niko Budi Anto (Indonesian Society of Applied Science (ISAS), 2023)
Currently, most lockers use keys or passwords for security. This has a high risk of being lost. The key that someone has is easily duplicated by other people, so the security is very low. Therefore, to prevent loss of items, a system is needed to secure the locker with fingerprint and facial recognition. Then the locker can be opened if the user's fingerprint and face match the registered data and there is information sent to the user via an application on the smartphone. Fingerprint testing is carried out by 2 users, the percentage is 95% from 20 tests. Face recognition testing based on distance is carried out with 3 resolutions. The HQVGA resolution is 240 x 176 with a distance of 5-60 cm, the percentage is 57% from the 35x test. The QVGA resolution is 320 x 240 with a distance of 5-70 cm, the percentage is 62.5% from the 40x test. The CIF resolution is 400 x 296 with a distance of 5-70 cm, the percentage is 65% of the 40x test. Time-based face recognition testing is carried out in the morning, afternoon and evening. In the morning the percentage is 60% from 5x tests. Daylight time percentage is 100% from 5x tests. At night the percentage is 80% from 5x tests. For the overall test, it can be concluded that this security system is successfully used and can be applied in everyday life because it can maintain user privacy and can monitor the condition of the locker.